1995
DOI: 10.1002/cne.903570110
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of thalamic projections to the supplementary motor area and the primary motor cortex: A retrograde multiple labeling study in the macaque monkey

Abstract: The exact knowledge on spatial organization of information sources from the thalamus to the supplementary motor area (SMA) and to the primary motor cortex (MI) has not been established. We investigated the distribution of thalamocortical neurons projecting to forelimb representations of the SMA and the MI using a multiple retrograde labeling technique in the monkey. The forelimb area of the SMA, and the distal and proximal forelimb areas of the MI were identified by electrophysiological techniques of intracort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 69 publications
10
36
0
Order By: Relevance
“…In general, the patterns of thalamocortical motor connections reported for macaques (e.g., Jones et al, 1979;Schell and Strick, 1984;Darian-Smith et al, 1990;Nakano et al, 1993;Shindo et al, 1995;Matelli and Luppino, 1996;Rouiller et al, 1999;Morel et al, 2005) are similar to those reported here for galagos. In both macaques and galagos, M1 receives dense inputs from VLp, less dense inputs from VLa, and only a few inputs from VM and VA. PMV receives dense inputs from medial VLp (area X), and less dense inputs from VLa, VM and MDmf.…”
Section: Thalamic Connections Of Motor Areas and Prefrontal Cortexsupporting
confidence: 87%
“…In general, the patterns of thalamocortical motor connections reported for macaques (e.g., Jones et al, 1979;Schell and Strick, 1984;Darian-Smith et al, 1990;Nakano et al, 1993;Shindo et al, 1995;Matelli and Luppino, 1996;Rouiller et al, 1999;Morel et al, 2005) are similar to those reported here for galagos. In both macaques and galagos, M1 receives dense inputs from VLp, less dense inputs from VLa, and only a few inputs from VM and VA. PMV receives dense inputs from medial VLp (area X), and less dense inputs from VLa, VM and MDmf.…”
Section: Thalamic Connections Of Motor Areas and Prefrontal Cortexsupporting
confidence: 87%
“…The origin of this variability is unclear, but it does not appear to be correlated with experimental factors such as survival time, total volume of virus injected, or number of sites injected. More importantly, similar variations have been observed in other studies that used conventional tracers to define origin of thalamic projections to the SMA (Schell and Strick, 1984;Wiesendanger and Wiesendanger, 1985a;Darian-Smith et al, 1990;Rouiller et al, 1994Rouiller et al, , 1999Shindo et al, 1995;Matelli and Luppino, 1996;Sakai et al, 1999Sakai et al, , 2002. In particular, the ratio of neurons labeled in basal ganglia recipient nuclei of the thalamus (VLo, VApc, VLm, VLcr) to neurons labeled in cerebellar recipient nuclei (X, …”
Section: Discussionsupporting
confidence: 75%
“…VPLo, VLcc) ranged from 0.9:1 to 6.4:1 (n ϭ 8) (Shindo et al, 1995;Matelli and Luppino, 1996). This range is nearly identical to that of GPi/dentate neurons labeled in the present study after virus injections into the SMA (0.6:1-6.3:1) (Table 2).…”
Section: M1supporting
confidence: 82%
See 1 more Smart Citation
“…Two days after the injection, thalamic neurons were labeled mainly in the VLo and VPLo that project to the MI directly. Relatively sparse labeling of these thalamic neurons indicates that a little longer time than 2 d may be needed for sufficient labeling of first-order neurons (for comparison with conventional tracing, see Holsapple et al, 1991;Shindo et al, 1995). At a 3 d postinjection period, both the GPi and the cerebellar nuclei contained labeled neurons.…”
Section: Discussionmentioning
confidence: 99%